Simultaneous in situ detection of apoptosis and necrosis in monolayer cultures by TUNEL and trypan blue staining - Perry, S W (BioTechniques, 1997)
A method for simultaneously detecting membrane permeability (characteristic of necrosis) and DNA fragmentation (characteristic of apoptosis) is described. By combining a common dye-exclusion method (Trypan Blue) with a commercially available terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end-labeling (TUNEL) labeling kit, we have succeeded in developing a novel methodology for obtaining permanently mounted slides of monolayer cell cultures double-labeled for DNA fragmentation and cell lysis. This method should facilitate in situ studies of cell death by allowing for a more accurate quantification of total toxicity in monolayer cell cultures and perhaps further enhance our understanding of the different mechanisms of cell death as well